Changes in healthcare utilisation during implementation of remote atrial fibrillation management: TeleCheck-AF project - Gawałko, Monika; Betz, Konstanze; Hendriks, Veerle; Hermans, Astrid N. L.; van der Velden, Rachel M. J.; Manninger, Martin; Chaldoupi, Sevasti-Maria; Hoogervorst, Henk; Martens, Herm; Pluymaekers, Nikki A. H. A.; Spreeuwenberg, Marieke D.; Hendriks, Jeroen; et al. (Netherlands heart journal, 2024)
Aim To evaluate changes in healthcare utilisation and comprehensive packages of care activities and procedures (referred in the Netherlands to as ‘ diagnose-behandelcombinatie (DBC) care products) during the implementation of the TeleCheck-AF approach (teleconsultation supported by app-based heart rate/rhythm monitoring) in a Dutch atrial fibrillation (AF) clinic. Methods and results In the Maastricht University Medical Centre+ AF Clinic, data on healthcare utilisation and DBC care products for patients consulted by both a conventional approach in 2019 and the TeleCheck-AF approach in 2020 were analysed. A patient experience survey was performed. Thirty-seven patients (median age 68 years; 40% women) were analysed. With the conventional approach, 35 face-to-face consultations and 0 teleconsultations were conducted. After the implementation of TeleCheck-AF, the number of face-to-face consultations dropped by 80% ( p < 0.001) and teleconsultations increased to 45 ( p < 0.001). While 42 electrocardiograms (ECGs) and 25 Holter ECGs or echocardiograms were recorded when using the conventional approach, the number of ECGs decreased by 71% ( p < 0.001) and Holter ECGs or echocardiograms by 72% ( p < 0.001) with the TeleCheck-AF approach. The emergency department patient presentations showed no statistically significant change ( p = 0.33). Overall, 57% of medium-weight DBC care products were changed to light-weight ones during implementation of the TeleCheck-AF approach. Patient satisfaction with the TeleCheck-AF approach was high. Conclusion The implementation of TeleCheck-AF led to a change in healthcare utilisation, a change from medium-weight to light-weight DBC care products and a reduction in patient burden. These results created the basis for a new reimbursement code for the TeleCheck-AF approach in the Netherlands.